Severe malaria with invasive bacterial infections in children in a paediatric service in sub-Saharan Africa - Kouéta, Fla; Kaboré, Aïssata; Nagalo, Kisito; Kaboret, Sonia; Dao, Lassina; Ouédraogo-Yugbaré, Solange Odile; Yé, Diarra (International Journal of Contemporary Pediatrics, 2016)
Background: Isolated or associated with other conditions, malaria is responsible for the death of a child every minute, mostly in sub-Saharan Africa. The main objective was to determine the epidemiological, clinical, and biological aspects and outcomes of severe malaria associated with invasive bacterial infections in children. Methods: A prospective analytical study was conducted at Charles de Gaulle Paediatric University Teaching Hospital between 1 July and 31 August 2014 in Ouagadougou, Burkina Faso. Children with severe malaria and invasive bacterial infections were included. Results: There were 140 children with severe malaria of whom 13.6% exhibited signs of invasive bacterial infection. Co-infection was significantly higher in children under 24 months (p = 0.02) who came from rural areas (p <10-6). Respiratory distress (p = 0.03), shock (p = 0.0006), severe anaemia (p = 0.03), hypoglycaemia (p <10-6), and high parasitaemia (p = 0.001) were significantly more frequent in cases of co-infection. Invasive bacterial infections included acute meningitis (11.4%) and pulmonary and digestive bacteraemia (3.2%). Identified pathogens were Streptococcus pneumoniae (10 cases), Haemophilus influenzae (six cases), and Salmonella typhi (three cases). The overall mortality rate was 6.4%; the mortality rate in co-infection cases was 16% vs. 1% in cases of isolated severe malaria (p = 0.0004). Conclusions: Invasive bacterial infections were frequently associated with severe malaria in children in our paediatric service. The prognoses were poor, and affected children must be systematically sought and appropriately treated to contribute to the reduction of mortality in children under five years of age.